Peranan Dinasti Abbasiyah Terhadap Peradaban Dunia - Iqbal, Iqbal (LP2M IAIN Palangka Raya, 2015)
Abbasiyah empire is which one empire in Islam. In History, Abbasiyah empire is top empire, so we called it as âThe Golden Age of Islamâ. This empire exist when Umayyah empire had fallen in Damaskus. Umayyahâs generation (Abdu al-Rahman al-Dakhil) escape from Abbasiyah empire and went to Andalusia. And automatically Abbasiyah empire exist in Damaskus. After Abbasiyah could controlled moslems in Damaskus, they changed governance center to Baghdad. In Baghdad, they developed sciences. They translated manuscript foreign languages to Arabic. Beside it, Abu Jaâfar al-Manshur was building Baitul Hikmah as a library and center of sciences development.